Sprouts Growing Healthy Habits: Curriculum Development and Pilot Study - Fisher, Meghan C.; Villegas, Elizabeth; Sutter, Carolyn; Musaad, Salma M.; Koester, Brenda; Fiese, Barbara H. (Frontiers in Public Health, 2019)
High rates of childhood obesity and the impact this has on children's health make it important to establish a healthy lifestyle during the early school years. This pilot study explored the impact of a newly developed healthy habits curriculum. The Sprouts: Growing Healthy Habits curriculum presents topics such as energy balance, healthy sleep habits, and food groups through short activities and interactive book-reading. A nonrandomized controlled experimental study design was used to assess impact. Fifty-seven children between 5 and 6 years of age participated from two elementary schools (36 from the intervention school, 21 from the control school). Knowledge was assessed pre- and post-intervention in five content areas (farm to table, bedtime routines, portion size, energy expenditure, sugar content of beverages) using card sorting, ranking, and sequence activities. Within- and between-school comparisons were conducted using differences between groups and mixed modeling approaches. Within the intervention school, significant increases in knowledge were observed for farm to table, sugar content of beverages, and bedtime routines. For the control school, there was a significant increase in knowledge of portion sizes. Considering between-schools, only change in knowledge of bedtime routines remained significant, with greater increases in the intervention school. Results seem promising given the short dosage of curriculum. Increases in knowledge of healthy habits in early childhood may help in promoting healthy behaviors and combatting the effects of obesity.